MEASURING INDONESIA’S COMMITMENT TO REDUCING PLASTIC WASTE IN THE SEA THROUGH A LEGAL APPROACH - Muhammad Insan Tarigan (Lambung Mangkurat Law Journal, 2021)
Indonesia is the second-largest producer of plastic pollution in the world after China. Based on the data in 2018, there were about 1.29 million tonnes plastic waste end up in the ocean per annum. With that regard, Indonesia needs to be responsible for the negligence in doing the international obligation to prevent, reduce, and manage the pollution that affect marine environment. The purpose of this research is to observe Indonesia’s commitment in reducing plastic pollution on marine environment by doing some legal approach. Therefore, this research conducted by normative juridical and using descriptive analysis. Data analysis that obtained is done through literature study. The conclusion of this research is that the commitment of Indonesian Government on preventing plastic waste in marine environment relatively needs to be improved. There are some of regulations which already targeted that has not established yet by Indonesian Government.